How Fast Is the Sessile Ciona? - Berná, Luisa (Hindawi Publishing Corporation, 2009)
Genomewide analyses of distances between orthologous gene pairs from the ascidian species Ciona intestinalis and Ciona savignyi were compared with those of vertebrates. Combining this data with a detailed and careful use of vertebrate fossil records, we estimated the time of divergence between the two ascidians nearly 180 My. This estimation was obtained after correcting for the different substitution rates found comparing several groups of chordates; indeed we determine here that on average Ciona species evolve 50% faster than vertebrates.